2023
DOI: 10.1097/phh.0000000000001790
|View full text |Cite
|
Sign up to set email alerts
|

Community-Dwelling Adults' Perceived Versus Actual Risk of Cardiovascular Disease, Body Mass Index, and Physical Activity Levels and Related Factors

Abstract: Context: The difference between actual and perceived risk levels shows distorted risk perception. Unrealistic perceptions of cardiovascular disease (CVD) risks and insufficient knowledge about CVD risk factors can not only hinder the adoption of a positive lifestyle change but also obstruct preventive efforts. Objective: The aim of this study was to evaluate the concordance between perceived and actual risks, body mass index (BMI), and physical activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…Considering the findings of the first stage of this study, it was determined that educational status and marital status did not show a significant difference. 28 The study found that after using HeartScore® and the Omaha System interventions, the percentage of individuals with impaired CVD risk perceptions decreased from 100% to 82.6%. However, perceptions of impaired BMI increased from 49.8% to 57.7%, while perceptions of realistic BMI decreased from 50.2% to 42.3%.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Considering the findings of the first stage of this study, it was determined that educational status and marital status did not show a significant difference. 28 The study found that after using HeartScore® and the Omaha System interventions, the percentage of individuals with impaired CVD risk perceptions decreased from 100% to 82.6%. However, perceptions of impaired BMI increased from 49.8% to 57.7%, while perceptions of realistic BMI decreased from 50.2% to 42.3%.…”
Section: Resultsmentioning
confidence: 95%
“…27 In the first phase of this study, only one-fifth of the participants were able to accurately identify their risks, and approximately half of them overestimated their risks. 28 There are a limited number of intervention studies in the literature aimed at improving impaired CVD perception. In all three studies, the interventions were nurse-led.…”
Section: Literature Reviewmentioning
confidence: 99%